Human protein requirements and infection stress among young children at the origins of agriculture - Ulijaszek, S (CRC Press, 2008)
The human need to meet the energy and protein needs of everyday life is fundamental to population health and survivorship, and is therefore an appropriate topic for Darwinian medicine to consider. The transition to agriculture involved major shifts in subsistence, resulting in change in diet from foods that humans may have been adapted to, to new ones that often challenged physiological adaptability. This change contributed to changes in patterns of human health that persist to the present day among rural agricultural populations of the developing world.